Assessing the Foreign Direct Investment Performance of Middle-Income Countries Using Data Envelopment Analysis with Translation Invariance - Runyu Yang; Youngbok Ryu; Mikhail V. Oet (Economies)
Foreign direct investment (FDI) is a primary vehicle for manufacturing transfer. Middle-income countries can benefit by effectively utilizing FDI to achieve technological development and economic equality and possibly address the middle-income trap issue. This study assessed the FDI performance of ten middle-income countries and examined the statistical relationships between their performance and their contexts: technological development, economic equality, and during the COVID-19 pandemic. For the former, we employed non-radial data envelopment analysis, taking advantage of its translation invariance property to derive efficiency scores; for the latter, we conducted a series of Kruskal–Wallis tests to examine the statistical relationships. According to the analysis results, we found that (a) most countries, except China and India, showed stable efficiency scores over time, (b) their efficiency scores were statistically significantly associated with the level of technological development (indicated by their technology lifecycle-based sigmoid curves) and economic equality (represented by Gini index and poverty indicator); and (c) their efficiency scores were not associated with the COVID-19 pandemic. The results imply that to improve their foreign direct investment performance, host countries may need to enhance their absorptive capacity in both the technological and economic domains.